OPTIMALISASI PERAN DAN FUNGSI LEMBAGA PENYELESAIAN DALAM SENGKETA PERTANAHAN DI KAWASAN PEDESAAN DALAM MEWUJUDKAN GOODWIL - Yudanto, Dika; Faried, Femmy Silaswati; -, Suwardi (jurnal.unprimdn.ac.id, 2023)
The development of information and communication technology has had a significant impact on various sectors of life, including the banking sector. The legal system has made essential safeguards to protect bank and customer data security. The latest information regarding developments in the Indonesian Kapital data leak case must be sought through trusted news sources or contacting authorities such as the OJK or Bank Indonesia to obtain accurate and up-to-date information. The Consumer Protection Law seeks to protect bank customers by limiting standard clauses that cannot be avoided in today's banking business world. The method in this research uses normative legal research. Issues in the banking world relate to the legal position of banking in cases of leakage of Indonesian Sharia Bank customer data and banking legal protection efforts that the legal system has carried out to protect the security of bank data and customer data. Two factors cause leaks of customer personal data, namely internal and external factors. Cases of customer data leakage are severe violations of privacy and information security. Banks, including Islamic banks, have a big responsibility in maintaining the confidentiality of customer data and protecting their personal information. If a data leak occurs, the bank could face legal and regulatory consequences, potentially harming its reputation. The method in this research uses normative legal research.